Różnorodność form pseudonimicznych w Internecie — próba klasyfikacji nicków - Misztal, Barbara (Słowo. Studia językoznawcze, 2010)
Electronic communication have become the reason for enormous changes in Polish language. The language of the Internet has got many features which have appeared due to the specificity of this medium. The necessity of logging in on the Internet has caused that nick-naming has become common and frequent and the linguistic material of this kind very rich. Nicks or Internet nicknames constitute a diversified in their form and meaning group of words, many of which display the characteristics of classical nicknames.